Review : Algoritma Kriptografi Sistem Keamanan SMS di Android - Maya Sari; Hindriyanto Dwi Purnomo; Irwan Sembiring (Institut Shanti Bhuana, 2022)
Abstract— The use of smartphones is very widespread in today's society. Android is widely liked by various circles of users as well as among smartphone manufacturers with its very interesting features. However, even though this smartphone technology has many features, users still have special considerations for SMS (Short Message Service) email. Unfortunately, this SMS feature has limitations, only in the security of exchanging confidential information, this system is needed to provide secure information exchange via Android-based SMS. Therefore, it is necessary to secure it using cryptographic methods and a high level of security is required. In this study, we will compare three cryptographic algorithms, namely AES (Advanced Encryption Standard), RSA (Rivest Shamir Adleman), and TEA (Tiny Encryption Algorithm) which is carried out by comparing the characteristics of the encryption algorithm, the results of which will be used for an Android-based SMS security system with better security. higher. Based on the findings of the review it can be concluded that TEA (Tiny Encryption Algorithm) is the best algorithm for this work for an SMS security system on Android.